Σχεδιασμός και Αξιολόγηση Πρωτοκόλλων για V2X Επικοινωνίες - Καναβός, Αθανάσιος (Πανεπιστήμιο Πελοποννήσου, 2025)
This PhD thesis presents the design, development, and performance evaluation of advanced resource allocation mechanisms for critical autonomous driving services across various scenarios with different performance requirements. V2X services are typically characterized by diverse network performance requirements in terms of latency, reliability, and throughput. Key international organizations have detailed several related use cases (UCs) and their corresponding requirements. This thesis presents a comprehensive analysis of the latest and most advanced autonomous driving UCs, along with a harmonized view of their requirements. It also examines the extent to which 4G and 5G networks can support these UCs concerning delay and spectrum needs. Critical services have stringent network performance requirements due to their role in safety features. Current fifth-generation (5G) base station schedulers do not differentiate between critical and non-critical automated driving applications. Consequently, as traffic loads increase, there is a significant decrease in performance for these critical services. This thesis introduces SOVANET, a beyond 5G scheduler that considers the Radio Access Network (RAN) load, as well as the requirements of critical automated driving applications, optimizing resource allocation to them compared to non critical services. The proposed scheduler has been thoroughly evaluated through extensive simulations and compared with the typical Proportional Fair scheduler. The results demonstrate clear benefits in SOVANET's performance for critical services. Previous work has been further expanded by introducing a new scheduler called SOVANET +. This scheduler also accounts for the RAN load, the requirements of critical automated driving applications, and channel quality to optimize resource allocation for critical services. The key feature of SOVANET+ is its ability to overprovision radio resources for vehicles with poor channel quality, down to a certain threshold. Below this threshold, the signal quality is so poor that overprovisioning wastes resources for all devices in a cell without yielding any real improvement for the critical service. SOVANET + is evaluated through extensive simulations in both urban and highway environments and compared against the typical Proportional Fair scheduler and the previous version of SOVANET. The results indicate that SOVANET+ performs effectively for critical services, providing significant improvements. To support this research, the ns- 3 simulator was extensively utilized as the tool for developing the resource allocation mechanisms mentioned.
Design and Performance Evaluation of Protocols for V2X Communications
Μ.Δ.Ε. 32
Keywords: Υπολογιστική νοημοσύνη; 5G συστήματα κινητής επικοινωνίας; Αρχιτεκτονική υπολογιστών; Συστήματα επικοινωνίας υπολογιστών; Computational intelligence; 5G mobile communication systems; Computer architecture; Computer communication systems; Educational technology; Εκπαιδευτική τεχνολογία; 6G; Scheduling; Resources Allocation; Critical V2N Services; Κυψελωτά Δίκτυα 6ης Γενιάς; Δρομολόγηση Πακέτων; Κατανομή Πόρων; Κρίσιμες V2N Υπηρεσίες